Interactive Collaborative Robotics: Second International Conference, ICR 2017, Hatfield, UK, September 12-16, 2017, Proceedings - Ronzhin, Andrey; Rigoll, Gerhard; Meshcheryakov, Roman (Lecture Notes in Computer Science, 2017)
This book constitutes the proceedings of the Second International Conference on Interactive Collaborative Robotics, ICR 2017, held in Hatfield, UK, in September 2017, as a satellite event of the 19th International Conference on Speech and Computer, SPECOM 2017.The 30 papers presented in this volume were carefully reviewed and selected from 51 submissions. This new conference invites researchers in the area of social robotics and collaborative robotics to share experience in human-machine interaction research and development of robotic and cyberphysical systems. Topics addressed are: assistive robots, child-robot interaction, collaborative robotics, educational robotics, human-robot interaction, medical robotics, robotic mobility systems, robots at home, robot control and communication, social robotics, as well as safety robot behavior.